2016
DOI: 10.1186/s12984-016-0142-9
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-enabled measurement of walking performance with a robotic exoskeleton: a pilot study

Abstract: BackgroundClinical scores for evaluating walking skills with lower limb exoskeletons are often based on a single variable, such as distance walked or speed, even in cases where a host of features are measured. We investigated how to combine multiple features such that the resulting score has high discriminatory power, in particular with few patients. A new score is introduced that allows quantifying the walking ability of patients with spinal cord injury when using a powered exoskeleton.MethodsFour spinal cord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 31 publications
0
29
0
Order By: Relevance
“…Six studies considered the mean distance and velocity achieved during a 6MWT showing a range from 47 to 129 m and 0.22 to 0.36 m/s, respectively (6, 17-20, 22) (Appendix I). Six studies considered the velocity required to complete a 10MWT (Appendix II), ranging from 0.25 to 0.38 m/s across 4 studies (17,18,20,21). The remaining 2 studies indicated that different injury levels can affect walking velocity (22), as can the level of assistance provided while walking (23).…”
Section: Ambulatory Outcomesmentioning
confidence: 99%
“…Six studies considered the mean distance and velocity achieved during a 6MWT showing a range from 47 to 129 m and 0.22 to 0.36 m/s, respectively (6, 17-20, 22) (Appendix I). Six studies considered the velocity required to complete a 10MWT (Appendix II), ranging from 0.25 to 0.38 m/s across 4 studies (17,18,20,21). The remaining 2 studies indicated that different injury levels can affect walking velocity (22), as can the level of assistance provided while walking (23).…”
Section: Ambulatory Outcomesmentioning
confidence: 99%
“…We estimated the probability of each infant belonging to the healthy reference population, represented by the YouTube cohort in this case, who are presumed to be healthy. We adopted the Naïve Bayes approach, previously used for clinical assessments of walking performance (Lonini et al, 2016). Under the assumption of normally-distributed features and feature independence, the joint probability of features over the reference population is:…”
Section: Discussionmentioning
confidence: 99%
“…infant deviates from the typical movements of healthy infants using a single score, the Naïve Gaussian Bayesian Surprise (Lonini et al, 2016). When we then tested this system on a clinical population (N=19) where the level of neuromotor risk was assessed by a clinician (low, moderate, and high), we found that Bayesian Surprise varied across participant groups.…”
Section: Introductionmentioning
confidence: 99%
“…Additional measurements that are not explicitly discussed here, but that can be conducted in conjunction with the proposed tests include clinical measures of walking performance [8] and other measures of human performance, such as might be used in the rehabilitation community. Furthermore, there are measures of vitals, including heart rate, blood pressure, oxygen demand, etc.…”
Section: Exoskeleton Performance Metricsmentioning
confidence: 99%